The effect of feedback according to habit theory on learning some wrestling holds for beginners - Rahim, L.Dr. Farhad Hassan (Sulaimani Journal for Humanities, 2025)
The importance of research in improving wrestlers' performance becomes clear through appropriate instruction based on feedback and habit theory, which helps correct the learning process and rectify any errors using suitable memory techniques.